A false positive 68Ga-DOTA-TATE involvement in an adrenal mass: Kaposi Sarcoma. (27th January 2023) - Ozbas, Burak; Gok, Mustafa; Etlec, Mustafa; Unal, Emre; Hacioglu, Aysa; Abdulrezzak, Ummuhan; Karahan, Ibrahim; Ozturk, Figen; Karaca, Zuleyha; Unluhizarci, Kursad
Abstract: Introduction: Pheochromocytomas (PCC) are rare tumors (0.8/100000) arising from adrenal medulla cells. The most common symptom of PCC is persistent high blood pressure. Apart from symptomatic cases, PCCs can also be asymptomatic and can be detected incidentally. Surgical treatment is urgent if catecholamine hypersecretion is detected. After the detection of hormonal hyperfunction in patients with PCC, the diagnosis is confirmed by anatomical and functional imaging. As we all know, there is no possibility of histopathological diagnosis before surgery in PCC. Therefore, rare coexistence of false positive Ga 68 -DOTA-TATE uptake and falsely high urinary catecholamine metabolite levels may lead to adrenalectomy of the patients without PCC. Here we describe a patient who underwent adrenalectomy with a prediagnosis of PCC but received a different pathological diagnosis. Clinical Case: A 50-year-old male patient who was diagnosed with AIDS after being investigated for fever of unknown origin was referred to the endocrinology department because of a mass in the left adrenal gland. The patient had complaints of headache, palpitation and sweating. On physical examination, there was a red nodular lesion on his face and a palpable lymph node in the inguinal region. His blood pressure was 160/100 mm-Hg, pulse was 100/min and body temperature were 37.1°C. Ambulatory blood pressure measurements showed that the patient's blood pressure was constantly high. Non-contrast CT showed a tumor of 20×15 mm in size (Hounsfield Unit:38) in the left adrenal gland (Fig-1 ). In terms of hormonal hyperfunction, no cortisol or aldosterone hypersecretion was detected, but urine normetanephrine was found to be 4 times higher than the upper normal limit (Table 1 ). Functional imaging revealed pathologically increased Ga 68 -DOTA-TATE uptake in the left adrenal mass and multiple lymph nodes (SUVmax 5.9 and 3.2) (Fig-1 ). The pathology of the patient who underwent simultaneous inguinal lymph node excision and adrenalectomy was reported as Kaposi sarcoma (KS). The patient is currently receiving treatment for AIDS and KS. Figure 1. In unenhanced computerized tomography (A); two nodules in soft tissue density, the largest of which was 17 mm in diameter were observed at the junction of the left adrenal gland body-medial limb were observed. In Ga68-DOTA-TATE PET CT (B), moderate-intense FDG uptake was observed in bilateral cervical, axillary, mediastinal and abdominopelvic lymph nodes, in addition, a nodular lesion with moderate hypermetabolic activity was detected in the left adrenal gland. Table 1. Laboratory findings of the patient on his first admission Abbreviations: Low Dose Dexamethasone Supression Test (LDDST), Aldosterone/Renin Ratio (ARR), Adrenocorticotropic Hormon (ACTH), Dehydroepiandosterone sulfate (DHEA-S). Conclusion: KS is a type of cancer that occurs especially in immunocompromised patients. Although there have been publications in the last decade suggesting that 18 F-FDG-PET/CT imaging may be beneficial in KS, there are no articles recommending the use of Ga 68 -DOTA-TATE. Upregulation of neuroendocrine genes has also been shown in publications investigating KS, which is thought to originate from endothelial cells. This may explain why there is Ga 68 -DOTA-TATE involvement in these lesions. Pheochromocytoma is referred to as "the great mimicker" in the articles of radiology and its similarity with all types of adrenal lesions causes PCC to not be excluded by anatomical imaging. We wanted to share these two diseases, which are very unlikely to come together and cause confusion, and explain the factors that can lead to this confusion.